Differences in Physical Education Learning Interests between Active and Inactive Students in Sports Extracurricular at SMK YPUP Makassar - Jahrir, Andi Sahrul; Aziz, Muhammad Ivan Miftahul (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the difference in interest in learning physical education between students who are active and inactive in sports and extracurricular activities at SMK YPUP Makassar. The approach of this research is quantitative with a comparative design. The sample consisted of 60 students who were divided into two groups, 30 active students and 30 students who were not active in sports extracurriculars. The sampling technique uses purposive sampling, which is to select students based on their involvement in sports and extracurricular activities. The instrument used in this study is a physical education interest and learning questionnaire that has gone through validity and reliability tests before being used. Data were analyzed using descriptive statistics and independent t-test tests. The results of the descriptive analysis showed that active students had an average learning interest score of 84.87 with a standard deviation of 5.02, while inactive students had an average of 66.50 with a standard deviation of 4.55. The results of the t-test showed that there was a significant difference between the two groups, with a significance value (p) of 0.000 (p < 0.05) and a mean difference of 18.367. The results of this study show that involvement in sports extracurricular activities is positively related to the level of interest in learning physical education. Therefore, schools need to encourage student participation in extracurricular activities as one of the strategies to increase interest in learning physical education subjects.